Aguapanela, a new tarantula genus from the Colombian Andes (Araneae, Theraphosidae) - Perafán, Carlos; Cifuentes, Yeimy; Estrada-Gomez, Sebastián (Zootaxa, 2015)
A new monotypic genus of Theraphosidae is described from Colombia: Aguapanela Perafán & Cifuentes gen. nov. with only the type species Aguapanela arvi Perafán, Cifuentes & Estrada sp. nov., from Caldas and Medellin, Antioquia, Colombian Andes. The new genus differs from other theraphosid spiders mainly in the presence of stridulatory setae on the palps and legs I and II, together with the presence of type III and IV urticating setae. Males lack a tibial apophysis on leg I and have a simple palpal bulb with the subtegulum less extended than usual in Theraphosinae, elongated curved embolus, ventrally concave, and with two prolateral keels very flat and developed on the dorsal edge. The female spermathecae have two digitiform elongated and granulated seminal receptacles attached to a semicircular wide membranous base. We describe, diagnose and illustrate the new genus and give some biological remarks. Morphological, systematic and biogeographic aspects are discussed. Chromatographic and electrophoretic profiles of its venom are analyzed.